KONVERSI LIMBAH PLASTIK HIGH DENSITY POLYETHYLENE (HDPE) MENJADI BAHAN BAKAR CAIR (BBC) MENGGUNAKAN KATALIS GAMMA ALUMINA (Î³-Al2O3) DAN ZEOLIT ALAM DALAM MULTISTAGE SEPARATOR - Aswan1,, Arizal; ., Fatria; ., Erlinawati; Wahab, Fathul; Manggarani, Anindyta (Politeknik Negeri Sriwijaya, 2020)
One of the dominant plastic waste in the world is plastic made from HDPE (High Density Polyethylene). HDPE plastic is often found in the form of plastic bags, food containers, pipe fittings, baby milk bottles, and others. This plastic is not biodegradable, so it can disturb the environment. If destroyed by burning, plastic waste will cause air pollution and cause global warming. One of alternative to reduce the number of this plastic waste is converting HDPE plastic into liquid fuel with a catalytic cracking process. This cracking process uses a Gamma Alumina (Î³-Al2O3) and Natural Zeolite catalyst to speed up the reaction to save energy consumption and improve the quality of the product result. The research was conducted by analyzing the effect of temperature variations ranging from 300, 350, 400, 450, and 500 oC. The result shown that the optimum temperature of pyrolysis High Density Polyethylene (HDPE) using Gamma Alumina (Î³-Al2O3) catalyst is 400oC with a density 0.7609 gr/cm3, viscosity 1.7760 mm2/s, and flash point 28.8oC. The optimum temperature of pyrolysis using Natural Zeolite catalyst is 450oC with a density 0.7282 gr/cm3, viscosity 2.8164 mm2/s, and flash point 30.9oC. The liquid fuel product from pyrolysis of HDPE plastic waste then analyzed by the GC-MS method, and it can be conclude that the liquid fuel product was a mixture of gasoline (C7-C12) and diesel (C13-C20)